Deformation sensing and electrical compensation of smart skin antenna structure with optimal fiber Bragg grating strain sensor placements. (1st March 2019) - Zhou, Jinzhu; Cai, Zhiheng; Kang, Le; Tang, Baofu; Xu, Wenhua
Abstract: Skin antenna structure is a kind of multifunctional composite structure in which printed antennas are integrated. This paper proposes a new smart skin antenna structure with embedded fiber Bragg grating (FBG) strain sensors. Utilizing the measured strains from limited FBG strain sensors, the deformation shapes are reconstructed by using a strain–displacement transformation, and the deteriorated radiation patterns caused by the deformations are compensated by using a strain-electromagnetic coupling mode which is derived and validated for the first time in the paper. Moreover, a two-step sensor placement method considering the information redundancy is proposed to determine optimal FBG strain sensor locations. The comparisons show that the two-step sensor placement method is advantageous in terms of the sensor distribution and computational cost. The fabrication process of the smart skin antenna structure was presented, and an experimental system with optimal sensor placements was developed. The measured results demonstrate that the reconstructed shapes agree well with the real ones, and that the deteriorated radiating patterns were almost completely restored to the desired ones. The proposed smart skin antenna structure which can provide the electromagnetic receiving-sending, structural deformation monitoring and electrical correction functions has a potential application prospect in the future mobile vehicle.